Minority Shareholder Protections and the Private Benefits of Control for Swedish Mergers - Holmén, Martin; Knopf, John D. (Journal of Financial and Quantitative Analysis, 2004)
Abstract Sweden has a high degree of separation of ownership from control through pyramids, dual-class shares, and cross-holdings. This increases the potential for private benefits of control. However, Sweden's extralegal institutions—tax compliance and newspaper circulation—are consistent with greater shareholder protection. Using data on Swedish mergers we find limited evidence of shareholder expropriation. Apparently, Sweden's extralegal institutions offset the drawback of weak corporate governance.